Enhancing Wire-EDM Performance with Zinc-Coated Brass Wire Electrode and Ultrasonic Vibration - Apiwat Muttamara; Patittar Nakwong (Micromachines, 2023)
This study aimed to investigate the performance of zinc-coated brass wire in wire-cut electrical discharge machining (EDM) using an ultrasonic-assisted wire on tungsten carbide. The research focused on the effect of the wire electrode material on the material removal rate, surface roughness, and discharge waveform. Experimental results demonstrated that using ultrasonic vibration improved the material removal rate and reduced surface roughness compared to conventional wire-EDM. Cross-sectional SEM of the white layer and discharge waveform were investigated to explain the phenomena of ultrasonic vibration in the wire-cut EDM process.